Alveograph and Mixolab parameters associated with Puroindoline‐D1 genes in Chinese winter wheats. (20th March 2013) - Chen, Feng; Li, Huanhuan; Li, Xiangnan; Dong, Zhongdong; Zuo, Aihui; Shang, Xiaoli; Cui, Dangqun
Abstract Background Grain texture is one of the most important characteristics of bread wheat and has a significant influence on end‐use qualities. Results Forty‐three Chinese cultivars were tested under three environments and used to characterise kernel hardness, Puroindoline‐D1 alleles and Alveograph and Mixolab parameters. The results indicated that SKCS hardness was positively correlated with Alveograph tenacity and P/L and Mixolab protein weakening (C2) and water absorption and negatively correlated with Mixolab starch gelatinisation (C3), amylasic activity (C4) and starch gelling (C5). Variance analysis showed that Puroindoline‐D1 had a significant impact on SKCS hardness and most Alveograph and Mixolab parameters. Furthermore, among three Puroindoline‐D1 genotypes, PINA‐null/Pinb‐D1a possessed the highest SKCS hardness, Alveograph tenacity and W and Mixolab stability and water absorption but the lowest Alveograph extensibility and G and Mixolab C3, C4 and C5. Pina‐D1a/Pinb‐D1a had the lowest SKCS hardness, Alveograph tenacity and W and Mixolab C2, water absorption and stability but the highest Alveograph extensibility and G and Mixolab C3, C4 and C5. Pina‐D1a/Pinb‐D1b possessed the lowest Mixolab C2 − C1, C3 − C2, C4 − C3 and C5 − C4. Conclusion Pina‐D1a/Pinb‐D1a was softer and had lower tenacity and water absorption. PINA‐null/Pinb‐D1a was harder and had higher tenacity and water absorption. Pina‐D1a/Pinb‐D1b had lower difference values among Mixolab parameters. © 2013 Society of Chemical Industry